Identification of Blood Lead Level of Motor Mechanic at Veteran Street, Makassar - Mulyadi, Mulyadi (Health Notions, 2017)
Being chronic poisoned by lead was usually caused by the occurrence of metal accumulation in human body. The sufferer would suffer headache, weary, depression, and if there was harder exposure, it could cause a problem in blood system (anemia), neural system, and kidney system that could cause kidney disease. Furthermore, this research aimed at knowing lead level in motor mechanicâs blood at along the Veteran Street, Makassar City and knowing its effect against blood pressure by utilizing cross sectional design. The samples of this research were 40 motor mechanics at Veteran Street, Makassar City who were chosen randomly. The collected data was analyzed by utilizing Chi-square and the results were: there was a significant correlation between age and lead level in blood, there was no significant correlation between the working hour, smoking behavior, the use of personal protective equipment, and lead level in blood, and there was a significant correlation between blood pressure and lead level in motor mechanicâs blood.